Two ancient theologians" interpretations of the withered fig tree (Mt 21:18–22) - Stander, Hennie F. (HTS teologiese studies, 2021)
This article is an investigation on how two theologians from the Early Church interpreted the withered fig tree, as narrated by the evangelist Matthew (Mt 21:18–22). The two theologians referred to are Origen of Alexandria, who belongs to the pre-Nicene era and represents the Alexandrian School, and Ps.-Chrysostom who belongs to the post-Nicene era, and represents the School of Antioch. Origen believed that when the fig tree withered, it referred to Israel’s withering. This interpretation of the narrative surrounding the withered fig tree was very common in the Early Church. Ps.-Chrysostom makes it very clear that he cannot agree with this interpretation, which was quite common in the Early Church. He stated that it is wrong to liken the fig tree to the synagogue of the Jews. He argues that Jesus could not curse the synagogue, because he said that ‘The Son of Man did not come to destroy, but to seek and save the lost’ (cf. Lk 9:56). Moreover, if the synagogue withered, fruitful branches such as Paul, Stephen, Aquila and Priscilla could not have sprouted from the roots. These names are proof that God did not entirely reject the Jewish people. Ps.-Chrysostom then offers a different explanation to the question why the fig tree withered: He points out that Adam used the leaves of a fig tree to cover his nakedness. When Jesus caused the fig tree to wither, he wanted to show that he can give Adam a new garment of water and spirit that glistens like snow. Christ gave back to Adam what the serpent had robbed him of, namely ‘the angel-like life, the luxuriance of paradise, the garment of incorruptibility’ (PC. cp. 4).Contribution: The primary goal of this article is to explore the exegetical practices of two ancient theologians who came from two different schools and from two different eras. This study shows how they interpreted the account of the withered fig tree (Mt 21:18–22), based on their respective theological perspectives.